Forage Food of Timor Deer (Cervus timorensis) in Manokwari, West Papua - Arobaya, AYS; Iyai, DA; Sraun, T; Pattiselanno, F (ANIMAL PRODUCTION, 2010)
Traditionally, back yard deer husbandry is well developed in some parts in Papua, though information on deer husbandry has not been provided yet.  Therefore, this study was aimed at highlighting the diet provided to the deer in back yard husbandry model in Manokwari. Survey method was approached by visiting eight deer back yard farmer respondents. Direct observation to the feeding site and semi-structured interview were carried out to learn about the deer management system, and identify the forage diet species consumed and served to the animals.  The results indicated five most common forage species consumed in the study; they were field grass, Imperata (Imperata cylindrica), elephant grass (Penisetum purpureum), king grass (Penisetum purpureopoidhes) and Melinis minutiflora depending on the location of farmed deer.   Drinking water was offered and feed supplement such as various leafs, food and vegetable left over and banana peel was provided by 62.5% of the respondents.  Food supplement was given two times per day (morning, evening) and (afternoon, evening). Forage food species consumed in the study sites were relatively more similar to the food in the natural habitat. (Animal Production 12(2): 91-95 (2010)Key Words: forage, food, Timor deer, Manokwari